"y'' + 2y' + y = 3{e^{ - x}}\\sqrt {x + 1}"
Let's find "{y_c}" , using auxiliary equation:
"\\begin{array}{l}\n{k^2} + 2k + 1 = 0\\\\\n{(k + 1)^2} = 0\\\\\n{k_1} = {k_2} = - 1\n\\end{array}"
Therefore "{y_c} = {C_1}{e^{ - x}} + x{C_2}{e^{ - x}}"
Let
"{C_1} = f(x),\\,{C_2} = g(x)"
Then
"y = f{e^{ - x}} + xg{e^{ - x}} \\Rightarrow y' = f'{e^{ - x}} - f{e^{ - x}} + g({e^{ - x}} - x{e^{ - x}}) + g'x{e^{ - x}}"
"\\begin{array}{l}\nLet\\\\\nf'{e^{ - x}} + g'x{e^{ - x}} = 0\\,\\,\\,(*)\n\\end{array}"
Then
"y' = - f{e^{ - x}} + g({e^{ - x}} - x{e^{ - x}}) \\Rightarrow y'' = - f'{e^{ - x}} + f{e^{ - x}} + g'({e^{ - x}} - x{e^{ - x}}) + g( - 2{e^{ - x}} + x{e^{ - x}})"
Substituting into our equation for y, y', y'', we have:
"\\begin{array}{l}\n - f'{e^{ - x}} + f{e^{ - x}} + g'({e^{ - x}} - x{e^{ - x}}) + g( - 2{e^{ - x}} + x{e^{ - x}}) + 2\\left( { - f{e^{ - x}} + g({e^{ - x}} - x{e^{ - x}})} \\right) + \\\\\n + f{e^{ - x}} + xg{e^{ - x}} = 3{e^{ - x}}\\sqrt {x + 1} \n\\end{array}" "- f'{e^{ - x}} + g'({e^{ - x}} - x{e^{ - x}}) = 3{e^{ - x}}\\sqrt {x + 1}"
with(*) we have
"\\left\\{ \\begin{array}{l}\n - f'{e^{ - x}} + g'({e^{ - x}} - x{e^{ - x}}) = 3{e^{ - x}}\\sqrt {x + 1} \\\\\nf'{e^{ - x}} + g'x{e^{ - x}} = 0\\,\n\\end{array} \\right."
From 2-nd equation:
"f' = - g'x"
Then
"g'x + g' - g'x = 3\\sqrt {x + 1} \\Rightarrow g' = 3\\sqrt {x + 1} \\Rightarrow g = 2\\sqrt {x + 1} (x + 1) + C"
"\\begin{array}{l}\nf' = - g'x = - 3x\\sqrt {x + 1} \\Rightarrow f = - \\frac{2}{5}\\left( {3x - 2} \\right)\\left( {x + 1} \\right)\\sqrt {x + 1} + {C_2}\\\\\ny = f{e^{ - x}} + xg{e^{ - x}} = \\left( { - \\frac{2}{5}\\left( {3x - 2} \\right)\\left( {x + 1} \\right)\\sqrt {x + 1} + {C_2}} \\right){e^{ - x}} + x\\left( {2\\sqrt {x + 1} (x + 1) + C} \\right){e^{ - x}}\n\\end{array}"
Comments
Leave a comment